Integration of Technological and Social Components in a Smart Urban Development Model: A Case Study of China - Almas Heshmati; Somayeh Koohborfardhaghighi; Christopher R. Summers (Institute of Labor Economics (IZA), 2022)
The path of urbanization around the world and in particular in China has been rapid. This study addresses measurement of a composite index of networking among key components of societal infrastructure and how it affects the process of urbanization. This study has a number of objectives. First we identify key determinants of public infrastructure components in China at the province level. Second a multidimensional index of the networking among the components is computed. The index belongs to parametric family of composite indices. It is composed of a number of components: Economic, Hospitality, Public Facilities, Human Development, and Communication Facility. Each component of the index is composed of a number of indicators. The index is used to rank provinces in China by development of level of the networking among public infrastructure components. In another step we estimate the effects of the composite index and its underlying components on urbanization. Finally, the findings is used to achieve smooth urbanization strategy for Chinese provinces. The empirical results are based on China's province level data covering the period 2005-2014. Our investigations provide evidence that integration of technological and social components are necessary to promote the development of an optimal and a smart urban development model. The necessity of an optimal and targeted urban infrastructure investment strategy emerges from our analysis. We briefly discuss the possible lessons learned from some of the successful provincial urbanization strategies.
Keywords: D31; I10; I20; I30; J13; 330; multidimensional index; composite index; principal component; urban infrastructure; China's provinces